2020
DOI: 10.1155/2020/7386239
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Epigallocatechin-3-Gallate in Hydrogen Peroxide-Induced Oxidative Damage in Chicken Lymphocytes

Abstract: Epigallocatechin-3-gallate (EGCG) is one of the fundamental compounds in green tea. The present study was to evaluate the protective effect of EGCG in oxidative damage and apoptosis induced by hydrogen peroxide (H2O2) in chicken lymphocytes. Results showed that preincubation of lymphocytes with EGCG significantly decreased H2O2-reduced cell viability and apoptotic cells with DNA damage, restored the H2O2-dependent reduction in total antioxidant capacity (T-AOC), glutathione peroxidase (GSH-PX), superoxide dism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 66 publications
0
14
0
Order By: Relevance
“…The results also noted a significant upraise in the level of thyroid hormones, and no study was recorded on the effect of BHA on the level of these hormones. However, it is believed that its role in this increase can be attributed to improving the health of the bird through increasing the level of SOD and CAT, which is one of the first lines of defense in the body (19), where superoxide dismutase works to break down free radicals and convert them to hydrogen peroxide. In contrast, catalase works to convert hydrogen peroxide into water and oxygen (20).…”
Section: Discussionmentioning
confidence: 99%
“…The results also noted a significant upraise in the level of thyroid hormones, and no study was recorded on the effect of BHA on the level of these hormones. However, it is believed that its role in this increase can be attributed to improving the health of the bird through increasing the level of SOD and CAT, which is one of the first lines of defense in the body (19), where superoxide dismutase works to break down free radicals and convert them to hydrogen peroxide. In contrast, catalase works to convert hydrogen peroxide into water and oxygen (20).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that pretreatment with an appropriate concentration of H 2 O 2 can significantly improve the proliferation, paracrine manner, antiapoptotic ability, and therapeutic effect of MSCs in liver fibrosis, skin wounds, and myocardial infarction [ 24 – 26 ]. However, a high concentration of H 2 O 2 is cytotoxic and will cause an increase in ROS, which may lead to irreversible oxidative damage to the cells [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that pretreatment with an appropriate concentration of H 2 O 2 can signi cantly improve the proliferation, paracrine manner, antiapoptotic ability, and therapeutic effect of MSCs in liver brosis, skin wound, and myocardial infarction [24][25][26]. However, a high concentration of H 2 O 2 is cytotoxic and will cause the increase of reactive oxygen species (ROS), which may lead to irreversible oxidative damage to the cells [27,28]. Therefore, exploring the optimal concentration of H 2 O 2 pretreatment is of great signi cance for improving the effect of NPMSCs in the treatment of IVDD.…”
Section: Introductionmentioning
confidence: 99%
“…. A high concentration of H 2 O 2 can induce a surge of intracellular ROS, which damages the organelles and results in cell cycle arrest and cell apoptosis[27]. However, pretreatment of transplanted cells with H 2 O 2 at appropriate concentrations can result in bene cial effects.…”
mentioning
confidence: 99%
See 1 more Smart Citation